2015
DOI: 10.1186/s13071-014-0615-2
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of infections with Giardia species and genotypes in well cared for dogs and cats in Germany

Abstract: BackgroundGiardia is now considered the most common enteric parasite in well cared for dogs and cats in developed countries. The ecology, epidemiology and clinical impact of infections with this parasite in such animals is still not fully understood due to variable results across different studies.MethodsFaecal samples were collected between 2009 and 2012 from privately owned cats and dogs in Germany presented to local veterinarians for a variety of reasons. Giardia positive samples were identified by microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 58 publications
6
34
0
10
Order By: Relevance
“…The Giardia positivity rates in dogs in our study was in the upper range of results reported in other German studies using similar methods where prevalence rates of 2%-30% (dogs) and 1%-25% (cats) were described (Barutzki & Schaper, 2011;Becker et al, 2012;Pallant, Barutzki, Schaper, & Thompson, 2015;Sommer, Rupp, Pietsch, Kaspar, & Beelitz, 2018). For humans, no cross-sectional study in Germany exists but the Giardia positivity rate of approximately 4% reported in our study is in good concordance with expected values (Caccio & Sprong, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The Giardia positivity rates in dogs in our study was in the upper range of results reported in other German studies using similar methods where prevalence rates of 2%-30% (dogs) and 1%-25% (cats) were described (Barutzki & Schaper, 2011;Becker et al, 2012;Pallant, Barutzki, Schaper, & Thompson, 2015;Sommer, Rupp, Pietsch, Kaspar, & Beelitz, 2018). For humans, no cross-sectional study in Germany exists but the Giardia positivity rate of approximately 4% reported in our study is in good concordance with expected values (Caccio & Sprong, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…In dogs, the host-specific assemblages C and D dominated, which has been described before in various studies [23, 24, 36, 5762]. Few dogs were (co)- infected with assemblage A, and the majority of these were identified as sub-assemblage AI.…”
Section: Discussionsupporting
confidence: 58%
“…La alta prevalencia en este estudio dado a sus condiciones ecológico-ambientales puede significar un potencial zoonótico transmitidas por mascotas (Thompson, 2000) y en estudios previos han evidenciado la presencia de cerca de ocho genotipos distintos de Giardia spp, con capacidad infecciosa inter-especie (Fava et al 2016), siendo los genotipos (A y B) lo mas importantes dado su capacidad de infección en perros (Canis familiaris), los gatos (Felis catus) y humanos (Fava et al 2016;Lalle et al 2005;Pallant et al 2015;Thompson 2000).…”
Section: Tabla 2 Variable Aspecto Y Positividad a Giardia Duodenalisunclassified
“…Sin embargo, se describe la frecuencia de Giardia spp., en los animales jóvenes (Bouzid et al 2015;Pallant et al 2015), pero Sierra (2015) no encontró asociación estadística respecto a la edad y la prevalencias de parásitos intestinales (p > 0,05) (Sierra 2015; Pallant et al 2015).…”
Section: Tabla 2 Variable Aspecto Y Positividad a Giardia Duodenalisunclassified